RADIACHECK: Implementation of Radioactive Radiation Monitoring Information System Using Waterfall Method at PT Petrokimia Gresik - Syahbana, Ahmad Naufal; Chotijah, Umi (Cattleya Darmaya Fortuna, 2024)
The use of radiation in industry has developed into a vital technology, especially in Non-Destructive Testing (NDT). At PT Petrokimia Gresik, radiation is used to check the quality of welding and internal structures, but the risk of exposure to radioactive radiation remains a major concern. This article discusses the development of Radiacheck, a web-based system for monitoring radioactive radiation using the Waterfall method. With features such as radiation calculator, history monitoring, and monthly reports, this system improves operational efficiency and work safety. In addition, this article also explains the implementation of features and system testing in detail based on PHP and MySQL technology.